« Faites la prévention, mais pas l’amour ! » : des regards féministes sur la recherche et l’intervention en éducation sexuelle - Boucher, Kathleen (Recherches féministes, 2003)
Cet article théorique pose un regard critique féministe sur la recherche et l’intervention récentes en matière d’éducation sexuelle au Québec et ailleurs. Deux courants de recherche se dégagent de la littérature scientifique : l’un concerne la prévention des problèmes sociaux liés à la sexualité et l’autre, la compréhension de la construction sociale de ces problèmes. L’attention accordée à des populations dites « à risque » appuie et renforce la thèse voulant que l’éducation sexuelle soit un phénomène marqué socialement, par le sexe et l’âge notamment, la sexualité des jeunes femmes faisant l’objet d’un plus grand contrôle social. Cette tendance s’observe dans plusieurs interventions d’éducation sexuelle : l’essentialisme, le naturalisme, l’hétérosexisme, l’âgisme, ainsi que les limites du discours préventif, sont abordés. L’auteure conclut en proposant l’adoption d’un modèle d’éducation sexuelle basé sur des principes féministes.
Keywords: 1900-1999; 1980-1989; 2000 à aujourd'hui; 2000-2009; amérique du nord; amériques; approches et analyses; canada; discipline; histoire et politique; hétérosexisme; périodes historiques; québec; rapports sociaux de sexe; ressource en ligne; régions géographiques; sciences de l'éducation; sexisme; sexualité; sexualité des femmes*; systèmes d'oppressions; systèmes éducatifs; thématiques; éducation sexuelle

Analyse sociopoétique de la réception mitigée de deux œuvres de Clémence Desrochers : le monde aime mieux... et Mon dernier show - Gauthier, Mélissa (Université Laval, 2003)
Keywords: 1900-1999; 1950-1959; 1960-1969; 1970-1979; 1980-1989; amérique du nord; amériques; arts; canada; chanson; discipline; femmes* artistes; monologue; mémoires/thèses; poésie; périodes historiques; québec; ressource en ligne; régions géographiques; sciences humaines; sociologie; études littéraires

Women of color and the reproductive rights movement - Nelson, Jennifer (New York University Press, 2003)
While most people believe that the movement to secure voluntary reproductive control for women centered solely on abortion rights, for many women abortion was not the only, or even primary, focus.Jennifer Nelson tells the story of the feminist struggle for legal abortion and reproductive rights in the 1960s, 1970s, and early 1980s through the particular contributions of women of color. She explores the relationship between second-wave feminists, who were concerned with a woman's right to choose, Black and Puerto Rican Nationalists, who were concerned that Black and Puerto Rican women have as many children as possible "for the revolution," and women of color themselves, who negotiated between them. Contrary to popular belief, Nelson shows that women of color were able to successfully remake the mainstream women's liberation and abortion rights movements by appropriating select aspects of Black Nationalist politics--including addressing sterilization abuse, access to affordable childcare and healthcare, and ways to raise children out of poverty--for feminist discourse.
Keywords: 1900-1999; 1960-1969; 1970-1979; 1980-1989; afro-féminisme; amériques; approches et analyses; discipline; femmes* de couleur; histoire; justice reproductive; militance; périodes historiques; régions géographiques; sciences humaines; sociologie; sofia; thématiques; états-unis

Chrétiennes et féministes! - Roy, Marie-Andrée (La pensée féministe au Québec : Anthologie 1900-1985, 2003)
Keywords: 1900-1999; 1980-1989; amériques; cours; fem1000; militance; mouvements des femmes*; mouvements féministes; premier cycle; périodes historiques; québec; religion; ressource en ligne; régions géographiques; thématiques

Queer theory and communication: from disciplining queers to queering the discipline(s) - Yep, Gust A.; Lovaas, Karen; Elia, John P. (Harrington Park Press, 2003)
Get a queer perspective on communication theory! Queer Theory and Communication: From Disciplining Queers to Queering the discipline(s) is a conversation starter, sparking smart talk about sexuality in the communication discipline and beyond. Edited by members of "The San Francisco Radical Trio," the book integrates current queer theory, research, and interventions to create a critical lens with which to view the damaging effects of heteronormativity on personal, social, and cultural levels, and to see the possibilities for change through social and cultural transformation. Queer Theory and Communication represents a commitment to positive social change by imagining different social realities and sharing ideas, passions, and lived experience. As the communication discipline begins to recognize queer theory as a vital and viable intellectual movement equal to that of Gay and Lesbian studies, the opportunity is here to take current queer scholarship beyond conference papers and presentations. Queer Theory and Communication has five objectives: 1) to integrate and disseminate current queer scholarship to a larger audience-academic and nonacademic; 2) to examine the potential implications of queer theory in human communication theory and research in a variety of contexts; 3) to stimulate dialogue among queer scholars; 4) to set a preliminary research agenda; and 5) to explore the implications of the scholarship in cultural politics and personal empowerment and transformation.
Keywords: 1900-1999; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; amériques; approches et analyses; communication; cours; disicpline; premier cycle; périodes historiques; queer; régions géographiques; soc2014; systèmes d'oppressions; thématiques; états-unis